Roman Catholicism and Eastern Orthodoxy: Can linguistic and semiotic analysis clarify their contrasts? - Sullivan, William J.; Tsiang, Sarah (LingBaW. Linguistics Beyond and Within, 2017)
The western and eastern branches of Christianity, broadly speaking Roman Catholicism (RC) and Eastern Orthodoxy (EO), have been formally separate for almost a millennium. Yet they share the fundamental dogmas laid down by the first ecumenical councils. History and politics are entwined in the disputes since the Great Schism of 1054, but even earlier there was controversy over basic dogmatic questions and other doctrinal matters. Some, like using leavened or unleavened bread for Consecration, are now considered “matters of custom,” not requiring argument. Other matters are said to block reunification. One of these is Purgatory, for which EO does not even have a term, making a direct comparison difficult. We begin our analysis with the RC teachings on Purgatory, its locus, characteristics, and functions, and provide a simple relational network that shows Purgatory in relation to the afterlife, in particular to Heaven and Hell. With EO we begin with the teachings about life after death and provide a first approximation of Heaven and Hell and their relation to Paradise and Hades, both in characteristics and functions. Again, a simple relational network is enlightening. A surface comparison between the two networks distinguishes between those beliefs about the afterlife that are shared between RC and EO and those parts which house differences. It is these differences that must be subject to careful semiotic analysis to discover whether they are etic and possibly serious but not grounds for mutual excommunication or emic and a true barrier to reunification. We leave the possibly lengthy semiotic analysis for a subsequent study.